The association between blood urea nitrogen to serum albumin ratio and 28 day in-hospital mortality in patients with chronic heart failure and sepsis: a pilot retrospective study - Ma, Ali; Zhang, Chen; Gong, Ying; Ma, Xueping; Yan, Ning (Frontiers in Cardiovascular Medicine, 2025)
AimsThe purpose of this study was to explore the relationship between blood urea nitrogen to serum albumin ratio and 28-day in-hospital mortality in patients with chronic heart failure complicated by sepsis admitted to the intensive care unit (ICU).MethodsThis retrospective study included 723 patients with chronic heart failure complicated by sepsis from the eICU database. Smooth curve fitting assessed the association between BAR and mortality. Multivariable Cox regression analysis was conducted to calculate the adjusted hazard ratio (HR) and 95% confidence interval (CI). Kaplan–Meier curves compared survival rates across BAR tertiles. Subgroup analysis was stratified based on relevant covariates and a forest plot was drawn to verify the stability of the results.ResultsAmong 723 chronic heart failure patients with sepsis, the 28-day mortality rate was 20.33% (147/723). After adjusting for confounders, with BAR as a categorical variable, patients in the highest tertile of BAR had a significantly higher death risk than those in the lowest tertile [HR: 1.87, 95% CI (1.09,3.19), p: 0.023]. When BAR was a continuous variable, each unit increase in BAR raised in—hospital mortality by 2% [HR: 1.02, 95% CI (1.01, 1.04), p = 0.0038]. Stratified analysis showed no interaction, and E—value analysis indicated robustness to unmeasured confounding, highlighting the stable and significant relationship between BAR and 28—day mortality in these patients.ConclusionIn the context of critically ill patients with chronic heart failure complicated by sepsis, there exists a significant correlation between blood urea nitrogen to serum albumin ratio (BAR) and 28-day mortality. Specifically, higher BAR levels are associated with an elevated risk of 28-day mortality in these patients. However, these findings require further research for confirmation.